The Relationship Between Aggressiveness of Students and Student's Cognitive Achievement in Islamic Religious Education (PAI) in SMA Negeri 1, Cirebon City - Tuti Alawiyah (UIN Sunan Gunung Djati Bandung, 2020)
Learning achievement which is influenced by the emotional level and learning activities of students makes researchers want to examine whether there is a relationship between aggressiveness and student achievement. There are negative and positive influences that arise at school, not all children who enter school are of good character, on the other hand there are children who attend school who come from families who pay less attention to children's interests in learning which often affect other friends. In education, aggressive behavior not only harms others but also harms oneself. This behavior can lead to bad character of students, especially in the subject of Islamic Religious Education that has been learned about the morals of fellow friends. The results showed a strong suspicion that there was a negative relationship between student aggressiveness and cognitive achievement, so it could be concluded that the higher the student's aggressiveness the lower the student's cognitive achievement